Competitive Advantage Approach Model Strategy Against Entrepreneurial Marketing Performance - Nurafrina Siregar (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
High sales are characterized by well-done marketing. The rapid change of times must be anticipated by SMEs in maintaining the sustainability of ulos cloth so that it does not become extinct. The concept of local wisdom innovation in the creative industry, variants, and quality of ulos fabrics is able to increase competitiveness in marketing ulos fabrics now and in the future. This study aims to determine the influence of local wisdom innovation, promotion strategies, entrepreneurial thinking, and business strategies on marketing entrepreneurial performance with competitive advantage as a mediation variable and marketing orientation as a moderation variable. Analysis tools used SEM. The sampling technique used is the census technique; all populations are sampled, totaling 221 SMEs actors of ulos cloth fostered by the Department of Cooperatives and SMEs in North Sumatra Province. The results show that business strategy, entrepreneurial thinking, local wisdom innovation, and promotional strategies significantly enhance competitive advantage and marketing performance, with competitive advantage acting as a partial mediator in these relationships. The findings imply that fostering cultural heritage through innovation and policy support, alongside the adoption of digital marketing, can enhance the competitiveness and sustainability of traditional textile SMEs such as ulos cloth in North Sumatra.